Are Young Physicians Have Problem in Job Insecurity? The Impact of Health systems' Changes - Luvy Kurniasari; Fendy Suhariyadi; Seger Handoyo (Journal of Educational, Health and Community Psychology, 2020)
Since 2013 Indonesia has adopted a national health system. This system changes directly affect the professional life of a physician. The system changes often lead to the rise of job insecurity on the individual involved. The purpose of this study is to investigate the impact of the health system's changes on young physician's job insecurity, based on the perception of payment, autonomy and meaningful work. The results of a literature review indicate that the factors that may affect the emergence of job insecurity are the perception of the payment and perceived autonomy. Research results show that Job Insecurity in physicians directly influenced by the perception of payment, the perception of autonomy and the meaningfulness of work, and then be indirectly affected by the perception of payment, the perception of autonomy with meaningfulness of work as mediation.Keywords: Job insecurity, perception of payment, perceived autonomy, meaningful work, physician.